2020
DOI: 10.21834/ebpj.v5isi3.2553
|View full text |Cite
|
Sign up to set email alerts
|

The TPSACK Framework Implementation in Measuring the Technological, Pedagogical, Skills and Content Knowledge by Using Courseware

Abstract: This study examines the implementation of the TPSACK courseware, which was developed with artistic skills practice to discover the Technological, Pedagogical and Content Knowledge of the Art and Design Education (ADE) students. The courseware was developed based on Dick and Carey Instructional Design Model (2009), which addresses instruction as an entire system, focusing on the interrelationship between context, content, learning and instruction. Respondents from 130 students were gathered to analyze the cours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Lecturers must inform students about the language of learning and the lesson's learning outcomes. It was found that students learn better in a specific content of pedagogies using illustrated methods that clearly explain the ideas and learning outcomes (Anuar et al, 2020). To ensure quality teaching, lecturers must delve into the learning process and segregate learning into smaller parts, then guide students on learning skills and ways to reinforce learning.…”
Section: Successful Teachingmentioning
confidence: 99%
“…Lecturers must inform students about the language of learning and the lesson's learning outcomes. It was found that students learn better in a specific content of pedagogies using illustrated methods that clearly explain the ideas and learning outcomes (Anuar et al, 2020). To ensure quality teaching, lecturers must delve into the learning process and segregate learning into smaller parts, then guide students on learning skills and ways to reinforce learning.…”
Section: Successful Teachingmentioning
confidence: 99%